A Challenging Giant Dermatofibrosarcoma Protuberans on the Face - Gimena Castro Pérez; Cintia Arias; Paula Luna; Irene Sorín; Luis Daniel Mazzuoccolo (Hindawi Limited, 2016)
Dermatofibrosarcoma protuberans (DFSP) is a malignant fibrohistiocytic tumor that appears exclusively on the skin. It is a low-grade malignant soft tissue tumor of subcutaneous tissues that has a propensity for local recurrence but seldom metastasizes. It may rarely occur on the head and neck accounting for less than one percent of total head and neck malignancies. We present a man with a giant DFSP on the face. Oncological, functional, and aesthetic aspects are set forth.